2016
DOI: 10.1039/c6ob01372d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of palmyrolide A macrocycles as sodium channel blockers towards neuroprotection

Abstract: Palmyrolide A is a neuroprotective macrolide isolated by Gerwick and coworkers in 2010. This natural product is known to suppress neuronal spontaneous calcium ion oscillations through its voltage-gated sodium channel blocking ability which is of significant interest in CNS drug discovery. Herein, we give a detailed account on total synthesis of (+)-palmyrolide A and synthesis of a focused library of macrocycles around the scaffold, followed by their biological evaluation. Use of the chiral pool approach, Zhu's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The anti ‐Me/ t ‐Bu structural motif has been reported for apratoxin A albeit in (5 S ,7 S )‐configuration. [ 11 ] Three types of intramolecular processes were used to construct the trans ‐ N ‐methyl enamide subunit of 1a / 1b : (a) a CuI‐catalyzed macroenamidation of a primary amide with a trans ‐alkenyl iodide followed by N ‐methylation [ 4a,b,d,f,h,5b ] or employing an N ‐methyl amide in the macroenamidation; [ 4g ] (b) a ring‐closing metathesis (RCM) [ 12 ] reaction of an N ‐allyl‐ N ‐methyl amide with an alkene followed by ruthenium hydride‐catalyzed alkene isomerization; [ 4c,f ] and (c) a TFA‐mediated dehydrative cyclization of an aldehyde with an N ‐methyl amide. [ 4e ] We reported total synthesis of two laingolide B stereoisomers and assigned the (2 S ,9 R ) absolute configuration for the naturally occurring 4 .…”
Section: Background and Originality Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti ‐Me/ t ‐Bu structural motif has been reported for apratoxin A albeit in (5 S ,7 S )‐configuration. [ 11 ] Three types of intramolecular processes were used to construct the trans ‐ N ‐methyl enamide subunit of 1a / 1b : (a) a CuI‐catalyzed macroenamidation of a primary amide with a trans ‐alkenyl iodide followed by N ‐methylation [ 4a,b,d,f,h,5b ] or employing an N ‐methyl amide in the macroenamidation; [ 4g ] (b) a ring‐closing metathesis (RCM) [ 12 ] reaction of an N ‐allyl‐ N ‐methyl amide with an alkene followed by ruthenium hydride‐catalyzed alkene isomerization; [ 4c,f ] and (c) a TFA‐mediated dehydrative cyclization of an aldehyde with an N ‐methyl amide. [ 4e ] We reported total synthesis of two laingolide B stereoisomers and assigned the (2 S ,9 R ) absolute configuration for the naturally occurring 4 .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 1 ] It is interesting to observe some trans ‐ N ‐methyl enamide‐containing macrolides possessing a tert ‐butyl carbinol moiety. [ 2 ] This small group of unique macrolides as depicted in Figure 1 includes palmyrolide A ( 1 ), [ 3‐5 ] laingolide ( 2 ), [ 6 ] laingolide A ( 3 ), [ 7‐8 ] laingolide B ( 4 ), [ 9‐10 ] and madangolide (structure not shown). [ 7 ] Palmyrolide A was isolated from a marine cyanobacterial assemblage composed of Leptolyngbya cf .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…anticancer, antibacterial, antifungal, immunosuppressant and more and thus have proven themselves to be extremely effective in the field of medicine. 3 In particular, 1,2,3-triazole-fused macrocycles have exhibited promising biological activities like anticancer [4][5][6] , antibacterial 7 , anti-inflammatory 8 , antiviral 9 and more [10][11][12] , and hence, the synthesis of triazole-based macrocycles has become a hot topic for researchers. Literature reports revealed that significant efforts have been attributed towards the synthesis of triazole scaffold involving Ag(I)-, Cu(I)-, Ru(II)-catalyzed azide-alkyne cycloaddition (AAC) reactions, microwave assisted reactions, ultrasound-promoted reactions etc.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Gerwick and co-workers reported the isolation of palmyrolide A ( 5 ), a structurally closely related 15-member macrolide from a cyanobacterial assemblage comprised of Leptolyngbya and Oscillatoria species collected at Palmyra Atoll, south of Hawaii [ 6 ]. One of the absolute configurations present in palmyrolide A was correctly assigned upon its initial isolation [ 15 ], and the absolute configurations of the remaining stereocentres were later established via total syntheses [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The structurally intriguing laingolides have attracted considerable attention from the synthetic community [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%